Inovasi Produk Usaha Mikro Kecil Menengah (UMKM) di Era Media Sosial - Dzaki Faishal Hidayat; Muhammad Irfan; Rendi David Sanjaya (STIKes Ibnu Sina Ajibarang, 2025)
This research explores product innovation carried out by Micro, Small and Medium Enterprises (MSMEs) in the era of social media. Social media has become a very important tool in expanding markets, strengthening brands, and supporting the innovation process of MSMEs. This research uses a descriptive method with a qualitative approach to analyze the role of social media in supporting the development of MSMEs. The research results show that digital literacy, cross-sector collaboration, and the use of data and social media analysis are key factors in increasing the competitiveness of MSMEs. The main recommendations include strengthening the digital capabilities of MSMEs, developing an innovation ecosystem, and optimizing digital marketing strategies for business sustainability.